Islamic Trade Financing and Poverty Mitigation: An Econometric Estimation Informing Islamic Development Bank Member Countries Considering Their Entrepreneurial Ecosystems - Sennanda, Musa; Mutunzi Kitunzi, Ahmed; Kasigwa, Gerald; Kintu, Ismail (International Journal of Applied Research in Management and Economics, 2023)
This paper is an analysis of the empirical effect of entrepreneurial ecosystems on the relationship between Islamic Trade financing (TF) and poverty trends in the context of Islamic Development Bank (IsDB) member countries. The study is an empirical analysis seeking to find out whether there is a statistical effect of the entrepreneurial ecosystems, measured as Global Entrepreneurship Index (GEI) scores, on the relationship between the Islamic Trade Financing dollar amounts by the IsDB (TF) and the GNI Per Capita, PPP, of all Islamic Development Bank (IsDB) member countries for the years 2009 to 2019. The research is designed as a desk-top longitudinal, correlation, employing the linear dynamic panel data GMM model as an estimator of the empirical relationships between the key variables of the study. The study results show that there is a significant positive relationship between the TF dollar amounts from the IsDB and the GNI Per capita, PPP, and that the ascending entrepreneurial ecosystem positively affects this relationship in the IsDB member countries. Therefore, countries that receive higher Islamic Trade Financing dollar amounts from the IsDB (IF), generally have more GNI Per capita, PPP (less poverty) than their counterparts, but ascending entrepreneurial ecosystem levels raises this positive relationship. It is, therefore, recommendable for IsDB member countries and all other interested countries to formulate policies that facilitate Islamic Trade financing to mitigate poverty and improve their entrepreneurial ecosystems for economic progress. This paper develops policy conversations that guide political discourse on policy topics of poverty mitigation and their relation to financing trade following Islamic products and services, while improving the entrepreneurial environment, thus generating information on policy choices of an Islamic financing nature.